SKENARIO PENGEMBANGAN SISTEM ANGKUTAN UMUM DI KOTA PALANGKA RAYA BERBASIS SISTEM TRANSPORTASI BERKELANJUTAN - Parasian Silitonga, Sutan; Riani, Desi (JURNAL SPEKTRAN; Vol 5 No 2 (2017): Vol. 5, No. 2, Juli 2017, 2017)
The concept of a sustainable and environmental transportation system emphasizes the widespread use of public transport, but the fact is very contrary to the development of the motorization trend era in Asian countries, especially the use of private vehicles motorcycles type. This is very closely related to the low functionality of public transport utilities, so it is not interesting to use. The success in the implementation of sustainable transportation policy is highly depended on the situation and condition of a city and the approach and understanding of the characteristics of society behavior, so that in the development of a city's public transport system there are not only technical and economic considerations but also community (social) preference consideration as an important part that unignoreable.  This research specifically aimed to respond the community preferences using Multinomial Logit  (MNL) model on several development scenarios of public transportation system in Palangka Raya based on scenario of road network pattern, traffic flow characteristic and land use type where the scenario analyzed using Analytic Hierarchy Procces (AHP) based on key parameters such as costs, construction and planning time, passenger capacity, flexibility, velocity, influence on city development and environment. The results of the study based on AHP analysis and regression analysis on community responses provided clear guidance on appropriate scenarios developed in Palangka Raya City where one of the main factor in the implementation consideration was the financial capability of the city. Final conclusion, the development of public transportation system scenario of Bus Rapid Transit (BRT) model equipped with feeder became a worthy considered option by the government of Palangka Raya City. Keywords : AHP, MNL, Development Scenario, BRT